Seasonality and trend in blood lead levels of New York State children - Talbot Thomas O; Haley Valerie B (BMC, 2004)
Abstract Background Environmental exposure to lead remains a significant health problem for children. The costs of lead exposure in children are estimated to be considerably more than other childhood diseases of environmental origin. While long-term trends in blood lead levels (BLLs) among children are declining, seasonal variation persists. Cross-sectional studies have found a peak in summer months. Part of this variation may be due to increased exposure to lead paint on window sills and through increased contact with soils containing lead during the summer. The current study represents the largest published population-based study on seasonality and trends in the BLLs of children to date. In addition, the results offer a comparison of recent data on seasonality of BLLs in New York State children, to studies conducted over the past three decades. Methods 262,687 New York State children born between 1994 and 1997 were screened for blood lead within 2 weeks of their first or second birthdays. Time series analyses of blood lead data from these children were conducted to study the seasonality and trends of BLLs. Results Children's blood lead values showed a distinct seasonal cycle on top of a long-term decreasing trend. The geometric mean BLL declined by about 24% for children born between 1994 and 1997. The prevalence of elevated BLLs in two-year-olds was almost twice that in one-year-olds over the time period. Nearly twice as many children had elevated BLLs in the late summer compared to late winter/early spring. In this and previous cross-sectional studies, the amount of seasonality as a proportion of the mean ranged between 15% and 30%. Conclusion Pediatricians should be aware of the seasonality of BLLs. For example, if a two-year-old receives a borderline result during the winter, it is possible that the levels would have been higher if he had been tested during the summer. However, physicians should continue to screen children at their normally scheduled well-child visits rather than delaying until summertime and possibly postponing the discovery of an elevated BLL. Age, season, and time trends still need to be considered in lead studies and result interpretation.